Peran Stakeholder pada Bauran Pemasaran Jasa Pendidikan - Frengki Frengki; Abdullah Abdullah; Kms Badarudin (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research is motivated by the need for schools based on religious education / Integrated Islamic schools that are more modern. as well as the proliferation of Integrated Islamic schools make the competition for marketing of educational services more varied in order to attract the interest of the community. The type of research used by the author is qualitative research that is descriptive by using interview, observation and documentation techniques in conducting data analysis, strengthened by data validity test using triangulation technique. The results of this research show that (1) the role of stakeholders in SMP IT Al-Furqon Palembang is quite good, this is due to cooperation starting from the principal, educators and parents, (2) the form of marketing carried out at SMP IT Al-Furqon Palembang using two ways, namely: Undifferentiated Marketing (marketing approach of educational services without distinction / without differentiation) and Concentrated Marketing (concentrated education service marketing approach (3) as for the supporting factors of SMP IT Al-Furqon school is under the auspices of foundation institutions therefore for oprasional and financial problems more independent, has a clear market segment.Support and trust from the community and alumni become a supporting factor in the marketing of educational services, the inhibition factor is that the school does not have a special team in the marketing of educational services, the lack of evaluation of the results of marketing educational services for improvement in the coming year and the cost of education that belongs to the middle class makes not all students/i join the school